EVOLUÇÃO LEGISLATIVA E JURISPRUDENCIAL DA TRIBUTAÇÃO BRASILEIRA DOS LUCROS, RENDIMENTOS E GANHOS DE CAPITAL AUFERIDOS NO EXTERIOR - Bez Batti, Gabriel (Revista de Direito Tributário Internacional Atual, 2022)
The article is an empirical research on legislative and jurisprudential development of the taxation of profits, gains and capital gains earned abroad. The objective is to analyze the background of the laws and the decisions ruled by the Judiciary and the administrative courts in order to unveil the Brazilian tax policy as regards this matter, and to settle both the tax position of the administrative courts and the application of the tax treaties by the Judiciary. The idea is to present the development of the legislation until the promulgation of Law n. 12,973/2014 and predict how the taxation of foreign profits, income and capital gains will be ruled by the judiciary.